Adaptive particle swarm optimisation for solving non-convex economic dispatch problems - Jamain N.; Musirin I.; Mansor M.H.; Othman M.M.; Salleh S.A.M. (Universiti Putra Malaysia Press, 2023)
This paper presents adaptive particle swarm optimization for solving non-convex economic dispatch problems. In this study, a new technique was developed known as adaptive particle swarm optimization (APSO), to alleviate the problems experienced in the traditional particle swarm optimisation (PSO). The traditional PSO was reported that this technique always stuck at local minima. In APSO, economic dispatch problem are considered with valve point effects. The search efficiency was improved when a new parameter was inserted into the velocity term. This has achieved local minima. In order to show the effectiveness of the proposed technique, this study examined two case studies, with and without contingency. 2017 Universiti Putra Malaysia Press.